Toward Optimal Management of Behavioral and Psychological Symptoms of Dementia: Insights From a COVID-19 Pandemic Experience - Debas, Karen; Beauchamp, Joanny; Ouellet, Christine (Frontiers in Psychiatry, 2021)
The first wave of SARS-CoV-2 has deeply affected long term care facilities in the province of Quebec. In response, governmental officials took protective measures, such as suspending visits and activities and even requiring residents to self-isolate to their room. Consequently, residents with major cognitive impairments were cut from their routine as well as from significant social interactions, support, and stimulation essential to their well-being. This isolation negatively affected many residents. For some of them, the loss of bearings resulted in newly or deteriorated behavioral and psychological symptoms of dementia (BPSD). These residents were then more at risk of contracting the virus or contaminating others. To face this challenge, hotels in the Greater Montreal area were transformed into temporary care facilities. As members of a multidisciplinary team specialized in the management of BPSD, we were asked to support the redeployed staff who had little experience in this domain. In this paper, we present the innovative tools implemented in this uncommon work setting. We also discuss factors identified as facilitating the care and treatment of people with BPSD. This experience leads us to propose avenues towards better BPSD management.